2015
DOI: 10.1159/000381848
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Proportion of Dementia-Free Life Expectancy in Hong Kong SAR

Abstract: Background: Estimations of life expectancies (LE) in health and ill health are important for planning future health care support. This study aimed at quantifying whether an increased LE is accompanied by an increase in the duration of life with dementia (DemLE) in Hong Kong SAR. Methods: Two parameters from a logistic model were used to fit the overall trend of the weighted prevalence of dementia. Abridged age- and sex-specific life tables and Sullivan's method were used to calculate dementia-free LE (DemFLE) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…As in previous studies, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] we first analysed the DemFLE and its proportion among people over 60 years of age in Jiangxi Province by sex differences. Compared with previous studies, our study showed similarities and differences in LE, DemFLE and DemFLE/LE [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The difference between China and other countries in the values of LE, DemLE and DemFLE may be caused by the influences of sampling error, different sampling methods, different diagnostic criteria and differences between Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous studies, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] we first analysed the DemFLE and its proportion among people over 60 years of age in Jiangxi Province by sex differences. Compared with previous studies, our study showed similarities and differences in LE, DemFLE and DemFLE/LE [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. The difference between China and other countries in the values of LE, DemLE and DemFLE may be caused by the influences of sampling error, different sampling methods, different diagnostic criteria and differences between Eastern and Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Before we started our research, some scholars conducted research on dementia-free life expectancy (DemFLE) for men and women in Australia [20,21], Belgium [22], Canada [23,24], France [25,26], Japan [27], the Netherlands [28], the United Kingdom [29][30][31], the United States [32][33][34][35], Brazil [36] and Hong Kong [37]. There are no studies on DemFLE in mainland China.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,9,11,12 In either case, the magnitude and rate of the increases in the demand for healthcare services relating to age-associated medical conditions has left many countries unprepared. [13][14][15][16][17][18] This has placed a significant financial burden on many governments. In Hong Kong, medical and health service expenditures have been increasing and now account for 16.8% of recurring government expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…In Hong Kong, with the measurement of chronic morbidity-free LE, DFLE, and DemFLE, studies have been done to examine the trends in health expectancies over the period 1996-2008) and 1998-2013(Cheung et al, 2015, which has implied an expansion of unhealthy states with the increase in LE in Hong Kong. A recent study drew a consistent conclusion that older population in Hong Kong would be more dependent in spite of a longer LE (Yu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%